Argon laser stapedotomy - Rebol, Janez (Acta medico-biotechnica, 2011)
Purpose: Presentation of our results of otosclerosis procedures undertaken with the argon laser. Methods: Argon laser stapedotomy was carried out in 47 patients in the last 18 months at our center. The procedure was conducted under general anesthesia using a transcanal approach. Pure-tone audiogram was done pre- and postoperatively. After each procedure, overclosure, closure of the air-bone gap and the average postoperative air-bone gap were calculated. Results: Average overclosure in all patients was 4.4 dB; average closure of the air-bone gap was 22.3 dB and average air-bone gap was 9.6 dB. Conclusion: Argon laser stapedotomy is a safe procedure that enables surgery without touching middle ear structures. Postoperative hearing results were satisfactory and stable; patients also had few problems with nausea and vertigo.
Keywords: Argon; hearing; Kirurgija; Laserji; Lasers; Otologic Surgical Procedures; Otološki kirurški postopki; Otosclerosis; Otoskleroza; sluh; stapedotomija; surgery; therapy; Zdravljenje